2005
DOI: 10.1111/j.1540-8159.2005.09155.x
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Dual External Direct Cardioversions Using Two Simultaneous 360‐J Shocks for Refractory Atrial Fibrillation Are Safe and Effective

Abstract: Failure of cardioversion of atrial fibrillation (AF) to sinus rhythm (SR) by standard external direct current cardioversion (DCC) may be due to failure of delivery of enough defibrillating energy rather than to the true refractoriness of AF. Ninety-nine patients with persistent AF (76 male; age 63.7 +/- 0.4 years; weight 113.1 +/- 25.1 kg) who failed standard DCC were included in this report. Under anesthesia, QRS synchronous shocks were delivered across anteroposterior electrodes in the following sequence: (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2005
2005
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 18 publications
2
10
0
Order By: Relevance
“…DSED has been previously reported to work for multiple etiologies of cardiac arrest. 6,8,[10][11][12][13][14][15][16] In one report of 2,990 consecutive patients undergoing treatment in the electrophysiology lab over a 3-year period, all 5 patients with VF refractory to standard defibrillation were successfully defibrillated with DSED. 10 A handful of prehospital and emergency department case reports and small case series in recent years describe DSED.…”
Section: Introductionmentioning
confidence: 99%
“…DSED has been previously reported to work for multiple etiologies of cardiac arrest. 6,8,[10][11][12][13][14][15][16] In one report of 2,990 consecutive patients undergoing treatment in the electrophysiology lab over a 3-year period, all 5 patients with VF refractory to standard defibrillation were successfully defibrillated with DSED. 10 A handful of prehospital and emergency department case reports and small case series in recent years describe DSED.…”
Section: Introductionmentioning
confidence: 99%
“…No thromboembolic, serious hypotension, or congestive heart failure events were reported. 12 To our knowledge, there have been no studies on the use of DSSC in VT patients with a pulse.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] Two retrospective cohort studies of patients with stable sustained VT revealed that 10.6% and 17% of patients developed hypotension during treatment, 7,8 findings that are consistent with a study of unstable VT. 9 In patients with unstable VT refractory to repeated shocks at standard doses, guidelines do not currently identify a rapid-acting low-risk therapy. Double sequential cardioversion, performed by delivering two shocks through two sets of pads as closely timed as possible, has been described for the management of patients with refractory atrial fibrillation (AF) [10][11][12][13] and VF. [14][15][16][17][18] Here we describe the successful use of double sequential synchronized cardioversion (DSSC) in a patient with unstable VT refractory to standard electrical cardioversion methods.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, it has been attempted with some success in out-of-hospital VF. 41,42 Timing of Shock Delivery Historically, early defibrillation has been a key link in the chain of survival and is important to minimize the elapsed interval until ROSC. 43 However, observational data suggests that defibrillation of a myocardium depleted of high energy phosphates resulted in higher incidence of post-defibrillation asystole.…”
Section: Energy Selection and Delivery Methodsmentioning
confidence: 99%